WHO FAVOURS THE GAY COMMUNITY? EXPERIMENTAL EVIDENCE USING CHARITABLE DONATIONS. (5th September 2017) - Sansani, Shahar; Rozental, Arik
ABSTRACT: In this paper, we conduct an experiment to determine the characteristics of individuals who are more likely to donate to a gay charity. After filling out a questionnaire that includes information on gender, ethnicity, and religiosity, as well as other factors, Israeli undergraduate students are asked to choose two out of four options: participation in a lottery, donation to a gay charity, donation to a religious charity, and donation to an education‐focused charity. Our most robust findings are that females and the less religiously observant are more likely to donate to the gay charity.